Martin Prozesky and well-being': retroactive and proactive perspectives on religion and ethics in the social transformation of South Africa - Smit, Johannes A. (Journal for the study of religion, 2018)
This article primarily outlines the discursive threads in Prozesky's Implications of Apartheid for Christianity in South Africa' in the book he edited, Christianity Amidst Apartheid: Selected Perspectives on the Church in South Africa ([1985] 1990); his first book, Religion and Ultimate Well-Being: An Explanatory Theory (1984); and his latest book, Conscience: Ethical Intelligence for Global Well-Being (2007). This is under three headings: Apartheid as Heresy; Explaining Religion; and Conscience Ethics. We conclude with some appreciative and critical reflections, that we believe, can take Prozesky's life-long project, further. This is positioned in the social transformation paradigm.Keywords: well-being, apartheid as heresy, explain religion, conscience ethics, religion and social transformation